CONSTRUCTION OF THE FIVE PILLAR LAW OF MUBADALAH IN THE PERSPECTIVE OF ISLAMIC MARRIAGE PHILOSOPHY - Munawaroh, Lathifah; Heradhyaksa, Bagas; Sadari, Sadari (SMART: Journal of Sharia, Traditon, and Modernity, 2022)
The philosophy of Islamic marriage is often overlooked by the perpetrators of marriage so that the divorce rate is always high. For example, the Central Statistics Agency (BPS) released data on the divorce rate in Central Java for various reasons, in 2020 it reached 65,815 divorces, in 2021 there will be no less than 65,722. Although comparing to the figures in the previous year, this figure has decreased slightly, it is still said to be high. One way to reduce this number is to require a complete understanding of the philosophy of Islamic marriage. The five pillar mubadalah can be jointly carried out by each husband and wife, so that household harmony can be achieved together. This paper seeks to examine this, where the type of research used is literature review with documentation techniques, the approach used is normative theology with content analysis techniques and drawing conclusions with a deductive thinking framework. The results of this study are that the philosophy of Islamic marriage is parallel to the maqasid sharia of marriage. Maqashid sharia marriage has two dimensions: maqashid ashliyyah or main maqashid, and maqashid taba'iyyah or complementary maqashid. The five pillar mubadalah are tips that need to be considered to create maqashid marriage and a philosophy of Islamic marriage at once